Teacher Qualities as Predictors of Mathematics Achievement - Charina G. Bardoquillo; Junna Jean B. Bardoquillo; Jerry Ann Yucaran (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Students’ mathematics performance continues to show considerable variation influenced by internal teacher-related factors, while empirical evidence regarding the roles of teacher self-efficacy, interest, and attitudes remains inconclusive. This condition raises questions about which teacher attributes contribute most significantly to students’ academic achievement. This study aims to analyze the relationships, evaluate the effects, and determine the relative contributions of teachers’ self-efficacy, interest, and attitudes to students’ mathematics achievement. This quantitative study employed a descriptive-correlational design to systematically examine the relationships among the variables. The study involved 40 mathematics teachers and 270 students as research participants. Data were collected through standardized surveys to measure teacher attributes and through documentation of students’ scores to assess academic achievement. The data were analyzed using Pearson’s r correlation to identify the strength and direction of relationships between variables. The findings indicate that teachers’ attitudes are significantly correlated with students’ mathematics achievement, whereas teachers’ self-efficacy and interest do not demonstrate significant correlations. The study concludes that teachers’ positive attitudes represent the dominant factor influencing students’ learning outcomes. The implications of this study highlight the importance of professional development programs that focus more specifically on strengthening teachers’ attitudes in order to support improvements in students’ mathematics learning achievement.